The Treatment of Textile Industrial Liquid with Activated Carbon - et. al., Darsini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The preparing innovation and upgraded modern area will influence the climate, decidedly or adversely. In light of the action, the material business of PT. Sinar Surya Indah Telukan Grogol, Sukoharjo created fluid waste which above quality norm. Subsequently, it is expected to deal with the wastewater. The goal of the examination is (a) to know the nature of fluid waste from, material industry and (b) to know the adequacy of dynamic carbo thickness for the decrease of fluid waste focus with boundaries Body 5, COD, Chrom (Cr), TSS (Complete Suspended Strong) and pH. The thickness of dynamic carbon was 0 cm; 5 cm; 7 , 5 cm; 10 cm; 12.5 cm; and 15 cm. The boundaries to be investigated were Body 5, COD, Chrom (Cr), TSS, and pH. A research facility test was done in the focal lab of MIPA, Sebelas Maret College. The outcome shows that there was a critical decrease od wastewater quality after prepared utilizing dynamic carbon, the level of decrease was as per the following: COD (83.86%), Body 5 (79.14%), TSS (46.09%) ), and Chrom (0%). The thickness for compelling dynamic carbon on 15 cm with squander volume as 1,5 liter; breadth 9 cm and stature 40 cm.